"Just another piece of paperwork": perceptions of clinicians on delirium screening following hip fracture repair elicited in focus groups. (June 2019) - Oberai, Tarandeep; Killington, Maggie; Laver, Kate; Crotty, Maria; Jaarsma, Ruurd
ABSTRACT: Background: Delirium is a complex clinical syndrome characterized by disturbed consciousness, cognitive function, or perception and associated with serious adverse outcomes such as death, dementia, and the need for long-term care. However, recognition and management of delirium is poorly prioritized even though it is the most frequent complication among patients undergoing surgery following hip fracture. The aim of this study was to understand clinicians' from orthopedic speciality perceptions in relation to recognition, diagnosis, and management of delirium. Methods: This was a qualitative study using in-depth focus groups discussions with clinical staff of one orthopedic unit within a level 1 trauma center, south of Adelaide, South Australia. Results: A total number of 17 individuals (14 nurses, 1 geriatric registrar, 1 nursing manager, and 1 speech therapist) participated in the focus groups. Four major themes were identified: (1) Delirium is important but can be hard to recognize and validate; (2) ambiguity on the use of delirium screening tool; (3) need of designated delirium care pathway; and (4) vital role of the family. Despite the initial lack of agreement on use of the objective tool to screen delirium, nurses did propose a number of ways that formal delirium screening could be included in routine nursing duties and existing nursing documentation. Conclusion: Although orthopedic nurses aim to provide effective care to patients experiencing delirium symptoms following hip fracture, they are doing so in the absence of structured screening, assessment, and multidisciplinary team approach. This study emphasizes the various barriers which need to be considered before attempting to change practice in this important area.